2018
DOI: 10.7126/cumudj.444396
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Slope of the Mesioangular Lower Third Molars and the Presence of Second Molar Distal Caries: A Retrospective Study

Abstract: Objective: The purpose of this study was to examine the relationship between the degree of mesioangular mandibular third molar teeth and the presence of distal caries in the second molar teeth. Materials and Methods: In this retrospective study, panoramic radiographs of 617 patients (328 females, 289 males) with impacted teeth in partially erupted mesioangular position were examined. The angle between the mandibular occlusal plane and the occlusal surface of the mandibular third molar was measured. Third molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Altan et al 29 (2018) have reported a significantly higher incidence of distal caries in the presence of a third molar in males than in females. In contrast, AlHobail et al 27 (2019) found that gender did not significantly affect the risk of distal surface caries in second molars because of third molars.…”
Section: In Cases Of Bacterial Invasion Of the Pulp Or Of Deepmentioning
confidence: 99%
“…Altan et al 29 (2018) have reported a significantly higher incidence of distal caries in the presence of a third molar in males than in females. In contrast, AlHobail et al 27 (2019) found that gender did not significantly affect the risk of distal surface caries in second molars because of third molars.…”
Section: In Cases Of Bacterial Invasion Of the Pulp Or Of Deepmentioning
confidence: 99%